Research Present Status and Outlook of Harmonic Reducer Testing Technology - Tao Menglun; Chen Yangpeng; Chen Dingfang; Wu Junfeng; Chen Fang; Li Bo; Mei Jie (Jixie chuandong)
As a kind of high-performance and precision transmission device with large transmission ratio,high transmission efficiency,high transmission precision,smooth transmission and low noise,harmonic reducer is more and more widely used in industrial robots,aerospace and other fields. Harmonic reducer needs to conduct a comprehensive test to ensure the performance of its reliability. Combined with domestic and foreign scholars’ research and progress on harmonic reducer testing technology,the exposition from the aspects of transmission precision,torque,stiffness,life time and integrated testing system are carried out,and the development trend of harmonic reducer testing technology is analyzed.